TOTAL VERTEX STRESS ALTERATION IN CYCLE RELATED GRAPHS - Kok, Johan; Shiny, Joseph; Ajitha, V. (Matematichki Bilten, 2021)
In the main this paper discusses the addition of an edge \(uv E(G)\) to a cycle graph \(C_n\) to obtain the 1-chorded cycle graph \(C_n^1\) such that the total vertex stress of \(C_n^1\) compared to the total vertex stress of \(C_n\) shows a maximum or minimum alteration over all \(uv E(G)\). Furthermore, results for wheel graphs, helm graphs, flower graphs, sunlet graphs, sun graphs and prism graphs are also presented. Finally a heuristic algorithm is proposed which determines the total vertex stress in a general graph \(G\).